Primary Spindle Cell Rhabdomyosarcoma of Prostate: A Case Report with Review of Literature - Ram Nawal Rao; Sanjay Kannaujia; Paramita Paul (Global Journal of Cancer Therapy - Peertechz Publications, 2017)
Primary spindle cell rhabdomyosarcoma of the prostate is an uncommon variant of embryonal rhabdomyosarcoma seen in pediatric age group mostly during infancy and childhood. Rhabdomyosarcoma (RMS) arising from prostate predominantly presents obstructive urinary symptoms. To date, only one case of the spindle cell variant of embryonal rhabdomyosarcoma of the prostate have been described in literature. The delay in diagnosis and a more aggressive behavior of this malignancy contributed to an eventually unfavorable outcome. Early diagnosis and complete surgical resection offering patients for the best possibility of survival.